Low-wage careers: are there dead-end firms and dead-end jobs? - Alexander Mosthaf; Claus Schnabel; Jens Stephani (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2009)
Using representative linked employer-employee data of the German Federal Employment Agency, this paper shows that just one out of seven full-time employees who earned low wages (i.e. less than two-thirds of the median wage) in 1998/99 was able to earn wages above the low-wage threshold in 2003. Bivariate probit estimations with endogenous selection indicate that upward wage mobility is higher for younger and better qualified low-wage earners, whereas women are substantially less successful. We show that the characteristics of the employing firm also matter for low-wage earners' probability of escaping low-paid work. In particular small plants and plants with a high share of low-wage earners often seem to be dead ends for low-wage earners. The likelihood of leaving the low-wage sector is also low when staying in unskilled and skilled service occupations and in unskilled commercial and administrational occupations. Consequently, leaving these dead-end plants and occupations appears to be an important instrument for achieving wages above the low-wage threshold. – – Mit repräsentativen verbundenen Arbeitgeber-Arbeitnehmer-Daten der Bundesagentur für Arbeit verdeutlicht diese Studie, dass nur jeder siebte Vollzeitbeschäftigte, der 1998/99 einen Niedriglohn (von weniger als zwei Dritteln des Medianlohns) bezog, bis 2003 den Niedriglohnsektor verlassen konnte. Bivariate Probit-Schätzungen mit endogener Selektion deuten darauf hin, dass die Aufwärtsmobilität für jüngere und besser qualifizierte Geringverdiener höher ausfällt, wohingegen Frauen deutlich weniger erfolgreich sind. Wir zeigen, dass auch die Merkmale des Beschäftigungsbetriebes die Aufstiegswahrscheinlichkeit beeinflussen. Insbesondere kleinere Betriebe und solche mit einem hohen Anteil von Niedriglohnbeschäftigten scheinen häufig Sackgassen für Geringverdiener darzustellen. Die Wahrscheinlichkeit, den Niedriglohnsektor zu verlassen, ist ferner relativ gering, wenn man in bestimmten (meist weniger qualifizierten) Jobs verharrt. Die Abwanderung aus solchen Betrieben und Beschäftigungen, die Sackgassen darstellen, dürfte deshalb ein wichtiges Mittel sein, um höhere Löhne zu erzielen.
Keywords: J30; J60; 330; low-wage employment; wage mobility; Germany